Rola orzecznictwa Trybunału Konstytucyjnego w kształtowaniu ram prawnych działalności spółdzielczych kas oszczędnościowo- -kredytowych - Mędrzecka, Joanna (PRAWO i WIĘŹ, 2023)
The paper reflects on the jurisprudence of the Polish Constitutional Tribunal, regarding cooperative savings and credit unions, and its legal effects. Four such rulings have been issued until now. The first decision K 53/07 of 24th March 2009 concerned provision of Article 15 of Financial Support for the Families in Obtaining Their First Apartment, amending an Old Cooperative Savings and Credit Unions Act of 1995, the second decision Kp 10/09 of 12th January 2012 concerned Articles 17 and 91 of the New Cooperative Savings and Credit Unions Act of 2009; the third U 2/12 of 18th February 2014 concerned Regulations of the Minister of Finance, establishing specific accounting rules for cooperative savings and credit unions, and the fourth K 41/12 of 31th July 2015 concerned all of the most important provisions of the New Cooperative Savings and Credit Unions Act of 2009. The first, the third and the fourth decisions were astonishing for credit unions members and activists. In the case resulting in second aforementioned decision, initiated by President of Poland Lech Kaczynski, who claimed that the New Cooperative Savings and Credit Unions Act of 2009 should be examined by Constitutional Court before its signing, one could observe a surprising action of the next President Bronislaw Komorowski who withdrew the most important part of the claim. On 13th September 2022 Minister of Justice submitte to Constitutional Tribunal a new claim regarding the provision of Article 97 of the Banking Guarantee Fund, Deposits Guaranteeing System and Mandatory Resolution Act (authorising the Banking Guarantee Fund to establish the Minimal Level of the Requirement for Own Funds and Eligible Liabilities MREL for the institutions) in the scope that concern cooperative savings and credit unions.